2014
DOI: 10.1155/2014/290381
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Cellular Antioxidant-Defence Preserves Diastolic Dysfunction via Regulation of Both Diastolic Zn2+and Ca2+and Prevention of RyR2-Leak in Hyperglycemic Cardiomyocytes

Abstract: We examined whether cellular antioxidant-defence enhancement preserves diastolic dysfunction via regulation of both diastolic intracellular free Zn2+ and Ca2+ levels ([Zn2+]i and [Ca2+]i) levels N-acetyl cysteine (NAC) treatment (4 weeks) of diabetic rats preserved altered cellular redox state and also prevented diabetes-induced tissue damage and diastolic dysfunction with marked normalizations in the resting [Zn2+]i and [Ca2+]i. The kinetic parameters of transient changes in Zn2+ and Ca2+ under electrical sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 64 publications
6
25
1
1
Order By: Relevance
“…Of note, under RNS exposure, the increases in FluoZin-3 intensity, which are associated with changes in [Zn 2+ ] i level, are in similar extent obtained in cardiomyocytes isolated from hyperglycemic heart, as previously demonstrated [25].…”
Section: Acute Increase Of Rns In Cardiomyocytes Induces a Marked Incsupporting
confidence: 85%
See 3 more Smart Citations
“…Of note, under RNS exposure, the increases in FluoZin-3 intensity, which are associated with changes in [Zn 2+ ] i level, are in similar extent obtained in cardiomyocytes isolated from hyperglycemic heart, as previously demonstrated [25].…”
Section: Acute Increase Of Rns In Cardiomyocytes Induces a Marked Incsupporting
confidence: 85%
“…They were fed standard chow ad libitum daily. The blood glucose level of STZdiabetic animals was significantly high compared to control rats while their blood insulin level was markedly lower compared to that of the control rats [25].…”
Section: Animal Model and Study Designmentioning
confidence: 71%
See 2 more Smart Citations
“…In our previous studies, we have shown that a cellular antioxidantdefence enhancement preserves both systolic and diastolic dyfunctions via regulation of basal-free Zn 2? level and leads to a balanced oxidant/antioxidant level in both heart and circulation and prevented the altered cellular redox state [10,53]. In these studies, incubation of cardiomyocytes with 10 lM ZnCl 2 exerted hyperphosphorylation in cardiac RyR2, as well as higher phosphorylation levels in both PKA and CaMKII in a concentration-dependent manner, similar to hyperglycemia.…”
Section: Discussionmentioning
confidence: 92%